Fragility fractures of the pelvis: should they be fixed? - Rommens, P M; Dietz, S-O; Ossendorf, C; Pairon, P; Wagner, D; Hofmann, A (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2015)
Due to the aging population, there is an increasing number of fragility fractures of the pelvis (FFP). They are the result of low energy trauma. The bone breaks but the ligaments remain intact. Immobilizing pain at the pubic region or at the sacrum is the main symptom. Conventional radiographs reveal pubic rami fractures, but lesions of the dorsal pelvis are hardly visible and easily overlooked. CT of the pelvis with multiplanar reconstructions show the real extension of the lesion. Most patients have a history of osteoporosis or other fragility fractures. The new classification distinguishes between four categories of different and increasing instability. FFP Type I are anterior lesions only, FFP Type II are non-displaced posterior lesions, FFP Type III are displaced unilateral posterior lesions and FFP Type IV are displaced bilateral posterior lesions. Subgroups discriminate between the localization of the dorsal instability. FFP Type I lesions are treated non-operatively. FFP Type II lesions are fixed in a percutaneous procedure when a trial of conservative treatment was not successful. FFP Type III lesions are treated with open reduction and internal fixation (ORIF). FFP Type IV lesions are treated with bilateral ORIF or with a bridging osteosynthesis. Iliosacral screw osteosynthesis is widely used, but has an elevated risk of screw loosening due to diminished bine mineral density. Transsacral bar osteosynthesis enable interfragmentary compression and does not have this danger of loosening. Bridging plate osteosynthesis is used as an additional fixation to iliosacral screw osteosynthesis. Lumbopelvic fixation is restricted to highly unstable lumbopelvic dissociations. More studies are needed to find the optimal treatment for each type of instability. Key words: pelvis, fragility fracture, diagnosis, classification, treatment.
Keywords: Male; Physical Therapy Modalities; retrospektivní studie; Fracture Fixation, Internal; vnitřní fixace fraktury; radiografie; Aged; mužské pohlaví; senioři; Pain Management; pánevní kosti; senioři nad 80 let; Bone Density Conservation Agents; lidé; ženské pohlaví; management bolesti; Humans; techniky fyzikální terapie; Aged, 80 and over; osteoporotické fraktury; Pelvic Bones; Retrospective Studies; inhibitory kostní resorpce; Female; Radiography; Osteoporotic Fractures